Clinical Aspects of Manic Episodes After SARS-CoV-2 Contagion or COVID-19 - Del Casale, Antonio; Modesti, Martina Nicole; Rapisarda, Ludovica; Girardi, Paolo; Tambelli, Renata (Frontiers in Psychiatry, 2022)
As COVID-19 pandemic spread all over the world, it brought serious health consequences in every medical field, including mental health. Not only healthcare professionals were more prone to develop anxiety, depression, and stress, but the general population suffered as well. Some of those who had no prior history of a psychiatric disease developed peculiar symptoms following infection with Sars-Cov-2, mostly because of psychological and social issues triggered by the pandemic. People developed traumatic memories, and hypochondria, probably triggered by social isolation and stress. Infection with Sars-Cov-2 has influenced the mental health of psychiatric patients as well, exacerbating prior psychiatric conditions. In this review, we focus on analysing those cases of mania in the context of bipolar disorder (BD) reported after COVID-19 disease, both in people with no prior psychiatric history and in psychiatric patients who suffered an exacerbation of the disease. Results have shown that COVID-19 may trigger a pre-existing BD or unmask an unknown BD, due to social and psychological influences (decreased social interaction, change in sleep patterns) and through biological pathways both (neuroinflammation and neuroinvasion through ACE-2 receptors expressed in the peripheral and central nervous systems (PNS and CNS respectively). No direct correlation was found between the severity of COVID-19 disease and manic symptoms. All cases presenting severe symptoms of both diseases needed specific medical treatment, meaning that they concur but are separate in the treatment strategy needed. This review highlights the importance of a now widespread viral disease as a potential agent unmasking and exacerbating bipolar mood disorder, and it can hopefully help physicians in establishing a rapid diagnosis and treatment, and pave the road for future research on neuroinflammation triggered by Sars-CoV-2.